Sustainable Agriculture 2009
DOI: 10.1007/978-90-481-2666-8_19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Traits Implicated in the Rhizosphere Competence of Fluorescent Pseudomonads: Description of a Strategy Based on Population and Model Strain Studies

Abstract: The lack of consistency of the beneficial effects of inoculated fluorescent pseudomonads has often been related to their bad survival in the rhizosphere. In this review, we describe the strategy followed over the last decade to study traits involved in the rhizosphere competence of these bacteria. The diversity of indigenous populations associated with plant roots was first compared to that of populations associated with uncultivated soils in order to identify traits that discriminate these populations. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…This hypothesis must be analysed by further studies including the three factors: biocontrol agent, pathogen and the host (tomato plant) in a simple and adapted models. In this optic Latour et al (2003), indicated that rhizospherecompetent pseudomonads had a specific metabolism characterized by the efficiency of the pyoverdine mediated iron uptake and by the ability to reduce nitrogen oxides.…”
Section: Root Colonization By Selected Fluorescent Pseudomonadsmentioning
confidence: 96%
“…This hypothesis must be analysed by further studies including the three factors: biocontrol agent, pathogen and the host (tomato plant) in a simple and adapted models. In this optic Latour et al (2003), indicated that rhizospherecompetent pseudomonads had a specific metabolism characterized by the efficiency of the pyoverdine mediated iron uptake and by the ability to reduce nitrogen oxides.…”
Section: Root Colonization By Selected Fluorescent Pseudomonadsmentioning
confidence: 96%
“…Observed lack of consistency of the biological control methods under field conditions may relate to abiotic factors or to soil microbial biodiversity which affects the establishment and colonization of the crops' rhizosphere by the biocontrol agents. Sufficient colonized biocontrol agents along with sustainable activity leads to successful plant protection (Latour et al 2009). Potato is considered an excellent model in developing modern biological control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…existing in soil or polluted water [6][7][8]. This prominent property makes these microorganisms attractive candidates for use in bioremediation and biocontrol activities [6,9].…”
Section: Introductionmentioning
confidence: 99%